2013
DOI: 10.5296/jse.v3i3.4187
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Gain Scores with Hierarchical Linear Models: A Value-Added Approach to Measure Teacher Effectiveness

Abstract: In this article, we predicted students' mathematics gain scores employing two-level hierarchical linear models (HLM) through value-added approach using data from one of the largest urban school districts in the United States of America. Effects of teacher quality or teacher effectiveness, characterized by teacher's certification in mathematics content area and teacher experience, were measured on students' gain scores. The results showed significant impact on mathematics gain scores due to teacher's content ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This study explores the individual effects of teacher level predictors: mathematics contentarea certification, advanced mathematics or mathematics education degree, and experience. Subedi and Swan [31] conducted similar study using two-level HLM analysis. This study extends their work using three-level HLM through value-added model in order to measure teacher effectiveness.…”
Section: Design Of the Studymentioning
confidence: 99%
“…This study explores the individual effects of teacher level predictors: mathematics contentarea certification, advanced mathematics or mathematics education degree, and experience. Subedi and Swan [31] conducted similar study using two-level HLM analysis. This study extends their work using three-level HLM through value-added model in order to measure teacher effectiveness.…”
Section: Design Of the Studymentioning
confidence: 99%
“…Similarly, Harris and Sass (2007) found that professional development in the form of content-specific training raised student achievement, using administrative data for the universe of third through tenth grade students in Florida. In another recent study, Subedi , Swan, and Hynes (2009) examined middle school gain scores in mathematics from a single school district and found significant positive effects for content certification in mathematics and teaching experience.…”
Section: Iia Education Literaturementioning
confidence: 99%